PENGARUH EXPERIENTAL MARKETING TERHADAP LOYALITAS TAMU DI HOTEL SAVOY HOMANN BIDAKARA - Endah Fitriyani; Endah Trihayuningtyas; Violetta Simatupang (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2017)
Competition of hotel accommodation business is increasing especially in Bandung. Some hotels are trying to win the market with one of the ways continually improving guest loyalty so as to provide maximum benefits to stakeholders. The purpose of this study is to obtain the data (1) experiential marketing carried in hotel, (2) guest loyalty in hotel, (3) the influence of experiential marketing towards guests loyalty at Savoy Homann Bidakara Hotel. The object of this research is experiential marketing (independent variable) and loyalty (dependent variable) with the unit of analysis is the guests who stayed at the Savoy Homann Bidakara Hotel. The method used in this research is descriptive and verification, and the research design of survey. Sample in this study are 100 respondents with technique of sampling is simple random sampling.Technique of data analysis used is path analysis. The results showed that experiential marketing and loyalty guest at the hotel get high score and there is the influence of experiential marketing towards loyalty guests at the Hotel Savoy Homann Bidakara simultaneouslywith significant value 0,00.Guest loyalty partially only influenced three sub-variables of experiential marketing, that is feel, act, and relate with the influence value of 86% and the remaining 14 % was influenced by other factors which were not examined.